The Nature and Mission of Islamic Educational Institutions (Madrasah) at Indonesia - Kulsum, Umi; Muslimah, Muslimah (CV. Creative Tugu Pena, 2024)
The process of fostering students' physical, spiritual and intellectual development towards the formation of Muslim personalities has developed from the simplest system to a modern Islamic education system. This is the essence of Islamic education. Judging from its aspects, systems and institutional forms, the development of Islamic education sometimes shows a tendency to be consistent with historical facts about Islamic education. The development of Islamic education tends towards an irregular trend and faces various challenges. Almuhafadhoh ala qodimis sholeh, wal akhdu bijadidil ashlah, this is an answer that might be able to answer the problems that exist in madrasah groups today, as it is understood that students' subtle abilities or abilities are very terrible in improving students' schooling. The current image of madrassas tends to be one that is simply strict, rather than a government-funded school that is popular for its knowledge. This can be changed by sticking to the foundation of the madrasah as a strict school position, without ignoring extensive information or in this case knowledge and abilities. Keywords: Mission Islamic Educational Institutions, Modern Islamic Education